Hybrids. - Bos, Saskia; Fletcher, Annie; Folkersma, Nina; Kellner, Clive; Serafijn, Q.S.; Szymczyk, Adam (Amsterdam : De Appel Foundation Amsterdam, 1997)
Mullican, Matt ; Dion, Mark ; Serafijn, Q.S. ; Grünfeld, Thomas ; Barney, Matthew ; Quinn, Marc ; Orlan ; Art Orienté Objet ; Kwaaitaal, Daniëlle ; Collishaw, Mat ; Höller, Carsten ; Eichhorn, Maria
biografie, bibliografie, filmografie, videografie
Hybrids, De Appel Foundation, Amsterdam, 1 juni tot en met 18 augustus 1996
Engels & Nederlands
boek